STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY E UMUR 33 TAHUN DI PUSKESMAS GARUNG WONOSOBO - Oktaviany, Fany; Indriani, Farihah; Aristyarini, Indrawati; Handayani, Wahyu (Jurnal Ilmiah Kesehatan, 2024)
The Maternal Mortality Rate (MMR) and Infant Mortality (IMR) are still relatively high in Indonesia. One of the government's efforts to overcome this is to use the SOAP method which is carried out in a continuous assessment (COC). The goal is to provide comprehensive midwifery care carried out in a continuity of care manner. The subject of this report is Mrs. E, 33 years old in the Garung Community Health Center area, where the assessment was carried out from March 9 2024 to April 22 2024. The results of the pregnancy assessment carried out 3 times, it was found that Mrs. E has a high risk of anemia. Maternity Care Mrs. E, no problems were found. BBL Care By. Mrs. E didn't experience any problems. The care of postpartum mothers was assessed 3 times at Postpartum Visit 1 (KF 1), there was a problem, namely Postpartum Anemia. Neonate Care By.Ny.E did not find any problems. Family planning (KB) care has no complications. Conclusion of midwifery care given to Mrs. E using the Continuity Of Care method can reduce the risk of complications in the mother. The suggestion from the study that has been carried out is that Midwifery Services continue to be provided to increase early detection and prevent complications